Experimental and numerical studies on the corrosion resistance and fatigue strength of short CFDST column - Farzana, O.A.; Cherian, R. Miji (Journal of Structural Engineering, 2024)
Concrete Filled Double Steel Tube (CFDST) columns are composite columns consisting of concrete sandwiched between outer and inner steel tubes with a central hollow portion. CFDST members can be used in marine structures, bridges, high-rise viaduct piers, composite piles in offshore structures and high-rise buildings, due to their strength and stability. The performance of these composite structures is greatly affected by the corrosion of steel tubes. The present study aims at experimental and numerical investigations on the corrosion behaviour of Mild Steel - (MS)-CFDST column and Epoxy coated Galvonized Iron (GI)-CFDST columns. It also aims at to investigate numerically the fatigue behaviour of CFDST column under reversed cyclic loading using validated finite element model. A total of 6 specimens, three no. of MS-CFDST and epoxy coated GI-CFDST each were cast, and immersion corrosion testing was conducted for a time period of 60 days. The corrosion rate and failure pattern of the CFDST columns were determined. The fatigue strength of corroded CFDST columns were also evaluated by finite element modelling.